Implementasi Pengorganisasian Pendidikan di Indonesia Terhadap Peningkatan Kualitas Pendidikan - Ahlal Kamal (PT. Ahlal Publisher Nusantara, 2025)
Educational organization has an important role in improving the quality of education in Indonesia. This article aims to analyze the implementation of educational organization in Indonesia, with a focus on policies, structures and practices of educational management, as well as their impact on improving the quality of education. This research uses the library research method, which relies on secondary data from books, journals and education policy documents. The analysis was carried out to explore the challenges that exist in the Indonesian education system, such as gaps in access to education between urban and rural areas, varying quality of school management, as well as obstacles to coordination between agencies. The results of the research show that although the organization of education in Indonesia has been implemented well in several regions, there are still big problems related to equitable distribution of education and efficient school management. Difficulties in coordinating policies and limited resources in less developed areas lead to disparities in education quality. However, by strengthening better regulations and implementing more effective policies, the quality of education in Indonesia can improve significantly. Therefore, increasing the competence of school principals, technology-based education management, and better decentralization policies are the keys to realizing a quality and equitable education system throughout Indonesia.